Two-dimensional ammonium distribution in sediment pore waters using a new colorimetric diffusive equilibration in thin-film technique - Metzger, E. (2021)
This study presents a new gel based technique to describe the pore water ammonium distribution through the sediment-water interface in two dimensions at a millimeter scale. The technique is an adaptation of the classical colorimetric method based on the Berthelot's reaction. After the thin film of the gel probe was equilibrated by diffusion either in standard solutions or in pore waters, a colorimetric reagent gel was set on the gel probe, allowing development of the characteristic green color. A flatbed scanner and subsequent densitometry image analysis allowed to determine the concentration distribution of ammonium. The gel probe was tested in the laboratory for two media, deionized water and seawater, within the range 0–3000 μM in NH4+. Detection limit is about 20 μM and accuracy about ±25 μM. The field validation was realized in a tidal mudflat of the French Atlantic coast by comparison with conventional pore water extraction and colorimetric analysis. The large range of concentrations and its applicability in continental and marine sediments suggest a wide range of applications of the technique for a reasonable cost.